W(h)ither the Association of South East Asian Nations (ASEAN)? W(h)ither constructivism? Fixity of norms and the ASEAN Way. (September 2019) - Collins, Alan
This article uses the reflection on the direction (whither) and health (wither) of constructivism and the Association of Southeast Asian Nations (ASEAN) that was witnessed in 2017 to see what these deliberations reveal about the fixity of norms and their contestation. The argument presented is that constitutive norms create fixed parameters of shared understandings but that within those parameters the meaning and application of the norm can be contested and debated. This insight helps to bridge the gap between conventional and critical constructivists and shows that the premise of jettisoning the ASEAN Way as necessary for ASEAN to achieve its ambitious community-building project is flawed. The argument relies on insights from the constructivist literature on norm degeneration to show how contestation is not one part of a norm's life cycle but rather a constant companion. However, norms are not just contested, but they have fixity, and here practice theory can help show that the social world is just as much about continuity as it is change. The ASEAN case study is timely as introspection about the efficacy of its constitutive norms – the ASEAN Way – was prominent in 2017 as ASEAN turned 50.